Introduction: Critical Approaches to 'Religion' in Japan: Case Studies and Redescriptions - Horii, Mitsutoshi (Religions, 2022)
This Special Issue of the online open access journal Religions is entitled “Critical Approaches to ‘Religion’ in Japan: Case Studies and Redescriptions” [...]